2016
DOI: 10.1111/pde.13028
|View full text |Cite
|
Sign up to set email alerts
|

Nail Psoriasis: A Systematic Evaluation in 313 Children with Psoriasis

Abstract: The prevalence of nail involvement was 32.3% in children with psoriasis. Clinical aspects in children are reported, as well as clinical associations. As in adults, nail psoriasis is closely associated with psoriatic arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 21 publications
1
22
0
6
Order By: Relevance
“…There are few studies on nail psoriasis in children, especially with appropriate methodology. Prevalence of nail involvement in this population varies among published studies (17%, 25.6%, 31%, 32.3%, 37.8%, 39.2% …”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…There are few studies on nail psoriasis in children, especially with appropriate methodology. Prevalence of nail involvement in this population varies among published studies (17%, 25.6%, 31%, 32.3%, 37.8%, 39.2% …”
Section: Discussionmentioning
confidence: 86%
“…Nail changes, isolated or associated with skin lesions, occur in 17%‐39.2% of children with psoriasis, but it has been suggested that detailed nail examination, applying the Nail Psoriasis Severity Index (NAPSI), might reveal some kind of alteration in up to 100% of these children . The most frequent are pitting, hyperkeratosis, splinter hemorrhages, oil drops, longitudinal grooves, crumbling, red spots in the lunula, and leukonychia …”
Section: Introductionmentioning
confidence: 99%
“…W przypadku płytek paznokciowych palców rąk występują w postaci objawu naparstka, na stopach częściej jako onycholiza i zgrubienie paznokci. Predysponowana do zajęcia przez proces łuszczycowy jest płytka paznokciowa palucha, a czynnikami ryzyka wystąpienia zmian paznokciowych są płeć męska, łusz-czyca dłoni i stóp, stopień nasilenia choroby oraz łusz-czycowe zapalenie stawów [21,22].…”
Section: Psoriatic Arthritisunclassified
“…Pitting of the nails is most common on fingernails, while onycholysis or thickening is more common on toenails. The big toe is also more predisposed to psoriatic nail lesions, and contributing factors include male sex, palmoplantar psoriasis, severe psoriasis and psoriatic arthritis [21,22].…”
Section: Typy I Odmienności Obrazu Klinicznegomentioning
confidence: 99%
“…Nail psoriasis affects 10–90% of adult patients with plaque psoriasis, and has been reported in 63–83% of patients with psoriatic arthritis (PsA) [2, 3]. In children with psoriasis the prevalence of nail involvement is 32.3% [4]. Nail involvement in psoriatic patients has a significant impact on their quality of life.…”
Section: Introductionmentioning
confidence: 99%